Decoding Servicescape from Ambience to Customer Satisfaction in Indian Urban Restaurants: A Quantitative Approach using Wilcoxon Signed-Rank Method - Kanjilal, Priyanka; Ray, Nilanjan; Majumder, Tanmoy; Chatterjee , Priyanshi; Roy, Sulagna (International Journal of Advances in Business and Management Research (IJABMR), 2025)
This study explores how ambient settings, specifically lighting, scent, music, and temperature, affect customer satisfaction in Indian urban restaurants. The research is based on the Stimulus-Organism-Response (S-O-R) and the Servicescape Model of Bitner, which intends to quantify expectations/perceptions differences between these sensory dimensions and whether they cause total satisfaction. The survey was given to 250 respondents employing a 5-point Likert scale to obtain expectations and perceptions of ambient conditions. A non-parametric test, which is applicable to ordinal data, the Wilcoxon Signed-Rank Test, was used to test significant differences in expectation and perception scores of each of the factors. Outcomes reveal statistically significant changes across all four ambient variables. Lighting, scent, and music exceeded customer expectations, indicating positive disconfirmation and enhanced satisfaction. On the other hand, temperature fell short of expectations, highlighting discomfort as a key dissatisfaction driver. The findings affirm that ambient cues are not peripheral but central to shaping experiential quality in hospitality settings.This study contributes by assimilating servicescape and S-O-R theories with a non-parametric statistical approach to empirically test expectation–perception gaps in an Indian context.